2013
DOI: 10.1186/2051-5960-1-43
|View full text |Cite
|
Sign up to set email alerts
|

Myelin alters the inflammatory phenotype of macrophages by activating PPARs

Abstract: BackgroundFoamy macrophages, containing myelin degradation products, are abundantly found in active multiple sclerosis (MS) lesions. Recent studies have described an altered phenotype of macrophages after myelin internalization. However, mechanisms by which myelin affects the phenotype of macrophages and how this phenotype influences lesion progression remain unclear.ResultsWe demonstrate that myelin as well as phosphatidylserine (PS), a phospholipid found in myelin, reduce nitric oxide production by macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 65 publications
0
57
0
Order By: Relevance
“…Previously, we found that myelin-derived lipids, such as cholesterol metabolites and fatty acids, partially account for the phenotype of phagocytes after myelin uptake418. Activation of the liver X receptor (LXR) and peroxisome proliferator-activated receptor β/δ (PPARβ/δ) underlies the impact of these lipids on the phenotype of phagocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that myelin-derived lipids, such as cholesterol metabolites and fatty acids, partially account for the phenotype of phagocytes after myelin uptake418. Activation of the liver X receptor (LXR) and peroxisome proliferator-activated receptor β/δ (PPARβ/δ) underlies the impact of these lipids on the phenotype of phagocytes.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis could account for the inflammatory activity of B-ECM as low molecular weight HA has been shown to be inflammatory while high molecular weight has been shown to be anti-inflammatory [36,83,84]. Additional proteoglycans such as myelin, which is abundant in brain ECM, have also been shown to be inflammatory at low molecular weight [34,37]. As HA has been shown to differentially regulate the inflammatory response depending on the molecular weight, solubilized U-ECM was further digested with hyaluronidase to determine if the HA molecules in the solubilized U-ECM play a role in the observed macrophage response (i.e., high PGE2 and low proinflammatory factor secretion).…”
Section: Discussionmentioning
confidence: 91%
“…First, in several of these in vitro paradigms, researchers load macrophages with myelin prior to applying inflammatory stimuli. In response to proinflammatory stimuli, these myelin‐laden macrophages almost invariably express anti‐inflammatory mediators and/or stop responding to the proinflammatory stimuli (Bogie et al, , ; Boven et al, ). Second, myelin stimulation in isolation invokes either no phenotypic activation or causes release of ROS and proinflammatory cytokines, with a few reports of subtle M2‐like activation in a cell type–specific manner (Kroner et al, ; Sun et al, ; van der Laan et al, ; van Rossum, Hilbert, Straßenburg, Hanisch, & Brück, ; Wang et al, ; Williams et al, ).…”
Section: Myelin–macrophage Interactionsmentioning
confidence: 99%